Mapping the Density, Diversity, and Digitization of the 21st Century: The Diagrammatic Architecture of MVRDV - Aslı Yücel; Hande Düzgün Bekdaş (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
“Cities have distinctive identities that vary physically according to their geographical location, demographics, culture, environment, and economic factors” (Nafa & Husain, 2021), thus, In today’s rapidly changing architectural environment, the need for new approaches to generate knowledge is increasingly important. In this era of growing complexities, diagrams have become a crucial tool in architecture, establishing the relationship between the abstract and the concrete. This research aims to explore how diagrams can be utilized to address the challenges related to density, diversity and digitization of the 21st century and provide insights into the diagram’s potential future practices. The qualitative content analysis method has been adopted, with data gathered from the unbuilt/diagrammatic works of MVRDV, a firm known for its innovative and speculative projects in the field. Findings revealed that diagrams are mostly utilized to shape forward-thinking designs, unite stakeholders, integrate data and technology into architectural spaces, and discuss environmental issues. This study emphasizes the potential of diagrams in linking architectural practice to contemporary challenges, suggesting that this potential could be further explored through various design examples and discourse in the future studies.